Life and Learning of Nepal’s Best Scientist: Insights from the Untimely Demise - Thakur, Rashmi; Chhetri, Surya (Journal of Advanced Research in English & Education, 2024)
The biographic research of a scientist holds significant value in the scientific community. Dr. Anjay Kumar Mishra is a renowned scientist and academic from Nepal, with a rich background in research and education. Despite all his efforts, he could not save his wife Tulika Jha from Cancer. The paper highlights the psychology of Dr. Mishra to express honest condolences through the innovation of a device to identify breast cancer. He believes that the treatment of cancer is only buying death at an expensive rate after the demise of his wife on 6th Jan 2024. He focused on early detection of cancer as the only way to overcome cancer and developing a dictation device for breast cancer along with associates. Altogether, he holds 21 copyrights from India and one patent design from the United Kingdom, Dr. Anjay Kumar Mishra’s editorial responsibilities are a testament to his profound impact on the academic community, as well as his unwavering commitment to advancing knowledge, promoting scholarly exchange, and upholding the highest standards of editorial integrity and excellence. His personality is characterized by a dedication to academic and research leadership, a commitment to addressing complex global challenges, and a strong focus on fostering knowledge exchange and innovation. His multifaceted engagement as a keynote speaker, editor, and author positions him as a prominent figure in the academic community, contributing significantly to the advancement of knowledge and the promotion of sustainable and inclusive development. The awards are insignificant in response to his contributions which can be evidenced as one of the best scientists of Nepal. Dr. Mishra’s experience in academia, research, and various roles within educational institutions demonstrate his expertise and his ability to effectively communicate complex concepts to diverse audiences.